Comparative Analysis of Structure and Material of Absorption Box on Rear Underrun Protection Device using Simple Additive Weighting - Reyhan, Rizki Nabil; Pranoto, Ethys; Tohom, Frans; Muthoriq, Ery; Hidayat, Dwi Wahyu (Jurnal Rekayasa Mesin, 2026)
Rear-end collisions between passenger vehicles and heavy trucks frequently result in high fatality rates due to underride events, in which the smaller vehicle slides beneath the truck. This underscores the need for improved passive safety systems, particularly the Rear Underrun Protection Device (RUPD), which serves to absorb impact energy. However, many existing RUPD designs only meet minimum regulatory requirements without optimizing energy absorption performance. This study aims to analyze and compare the influence of varying material types and structural configurations of the energy absorption box on the RUPD’s energy absorption capability. The evaluation focuses on deformation, stress distribution, and absorbed energy under impact loading conditions. The methodology involves three-dimensional modeling using SolidWorks and finite element method (FEM) simulations in Ansys. Materials including ASTM A36 steel, AISI 1020 steel, and Aluminum 2024 are combined with honeycomb structural variations. Simulations are conducted in accordance with UN ECE R.58 standards. Furthermore, the Simple Additive Weighting (SAW) method is applied to determine the optimal design. The results indicate that both material selection and structural configuration significantly affect energy absorption performance, with the honeycomb structure using filler with Aluminum 2024 demonstrating superior capability. This study contributes to the development of more effective RUPD designs aimed at enhancing road safety.